Analisis Pengaruh NIM, CAR, NPF, Dan DER Terhadap Profitabilitas (ROA) Pada Bank Umum Syariah (BUS) Periode 2017-2022 - Yanti, Silvi; Suryani, Suryani; Jajuli, Sulaeman (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
The development of Islamic Commercial Banks is in line with the existing problems, in this observation it was found that there were several problems including 1. There were fluctuations in the value of Net Interest Margin from 2017-2022 at Islamic Commercial Banks. 2. There is a decrease in ROA in 2020 at Islamic Commercial Banks even though CAR has increased. 3. There was a decrease in ROA in 2020 at Islamic Commercial Banks while NPF decreased and there were ups and downs in the value of NPF for the 2017-2022 period. 4. DER which tends to be large from 2017-2021 can result in a decrease in ROA at Islamic Commercial Banks. The study aims to analyze the effect of NIM, CAR, NPF and DER on ROA at BUS for the period 2017-2022, with quantitative methods, 30 secondary data samples through BUS financial reports and time series and cross section (panel) regression analysis techniques that meet the requirements of several model tests, presented in the EViews 12 application. The results showed that NIM had an effect on ROA as evidenced by the results of the T test count greater than the T table (value 2.712288> 2.073873) with a significance value of 0.013 <0.05. Furthermore, CAR has an effect on ROA as evidenced by the results of the T test which is greater than the T table (value 4.432700>2.073873) with a significance value of 0.0003 <0.05. NPF also affects ROA as evidenced by the results of the T test which is greater than the T table (value 2.273027>2.073873) with a significance value of 0.0348 <0.05. On the other hand, DER has no effect on ROA as evidenced by the results of the T test which is smaller than the T table (value 0.643701>2.073873) with a significance value of 0.5275>0.05. In the F test together NIM, CAR, NPF and DER affect ROA by 53.46% with a probability value of 0.000780 <0.05.